Emotional intelligence in bipolar-I-disorder: A comparison between patients, unaffected siblings, and control subjects. Issue 1 (2020) - Frajo-Apor, Beatrice; Kemmler, Georg; Pardeller, Silvia; Huber, Markus; Macina, Christian; Welte, Anna-Sophia; Hoertnagl, Christine; Hofer, Alex
Abstract: Background: Impairments in social and nonsocial cognition have been demonstrated in both patients suffering from bipolar disorder (BD) and their unaffected relatives and might therefore represent a heritable marker of risk. This study investigated the relevance of emotional intelligence (EI) as part of the emotion processing domain of social cognition in this regard. Methods: A total of 54 outpatients suffering from BD, 54 unaffected siblings, and 80 control subjects were investigated using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) and the Brief Assessment of Cognition in Schizophrenia (BACS). Analyses of covariance (ANCOVAs) were performed with adjustment for the BACS composite score. The three groups were compared by one-way analysis of variance or chi-square test, depending on the variable type. As the three groups differed significantly in their level of education, additional ANCOVAs with adjustment for education were performed. Results: Patients achieved significantly lower levels of overall EI and overall nonsocial cognitive functioning compared to unaffected siblings and controls, whereas performance of the latter two groups was comparable in both domains. Conclusions: Due to comparable levels of EI in unaffected siblings of patients suffering from BD and control subjects, EI assessed by means of the MSCEIT does not represent an endophenotype for BD.